KARAKTERISTIK INTERNAL DAN KARAKTERISTIK EKSTERNAL PETANI KELAPA SAWIT DI DESA BULUH RAMPAI KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU - Riawati, Riawati; Rosnita, Rosnita; Yulida, Roza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The study aims to analyze the dynamics of farmer groups Enggal Jaya in the Village Buluh Rampai Districts Seberida District of Indragiri Hulu. This research was conducted in the Village of Buluh Rampai Districts Seberida District of Indragiri Hulu. This research was conducted in the Village of Buluh Rampai Districts Seberida District of Indragiri Hulu. The research was conducted from March 2015 until January 2016 and the methods used in this research is survey method with census sampling. Data analysis was performed using Likert Analysis and Spearman's Test. The results show the internal characteristics of farmers such as age, education level and number of dependents has a strong relationship and significant impact on the dynamics of farmer groups Enggal Jaya. On the external characteristics of farmer extension intensity and the amount of resources have a strong relationship and significant impact on the dynamics of farmer Enggal Jaya.  Keywords : Dynamics, Farmers, Internal, External